Compactness vs. Sprawl Revisited: Converging Views - Reid Ewing; Harry W. Richardson; Keith Bartholomew; Arthur C. Nelson; Chang-Hee Christine Bae (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper examines the relative merits of compact cities or urban sprawl (suburban settlement patterns) as a spatial solution to environmental problems (such as climate control), automobile dependence, economic development, infrastructure costs and the quality of urban life.
Keywords: R14; 330; compact cities; sprawl; vehicle miles traveled; carbon emissions; infrastructure costs; residential preferences; commuting times